2010
DOI: 10.1159/000321531
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Tear Film Function after Pterygium Operation

Abstract: Objective: To assess changes of tear film function in patients with pterygium after pterygium excision combined with limbal-conjunctival autograft transplantation. Methods: Sixty eyes of 60 patients were entered in the study. The Schirmer test, tear breakup time (BUT) and mucus fern test (MFT) were evaluated in the patients before and after pterygium excision combined with limbal-conjunctival autograft transplantation. Results: Compared with the opposite healthy eyes, the BUT and MFT in the eyes with pterygium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…Tear osmolarity, however, deteriorated after 12 months in cases of pterygium recurrence. The authors inferred that pterygium excision improves tear film function, supporting similar findings of two previous studies [23,24], and concluded that pterygium recurrence leads to dry eye.…”
Section: Discussionsupporting
confidence: 82%
“…Tear osmolarity, however, deteriorated after 12 months in cases of pterygium recurrence. The authors inferred that pterygium excision improves tear film function, supporting similar findings of two previous studies [23,24], and concluded that pterygium recurrence leads to dry eye.…”
Section: Discussionsupporting
confidence: 82%
“…However, conflicting results have also been reported [5, 18]. In 2 previous studies with follow-up periods of 1 [10] and 2 [11] months, the results of the BUT and mucus fern tests, but not the Schirmer test, improved significantly over their respective baseline values following pterygium excision. Conversely, another study with a 6-month follow-up period found no difference between the Schirmer and BUT test results at baseline and those obtained 1 and 6 months after surgery [19].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used tear function tests, such as the Schirmer test or tear breakup time (BUT), to investigate the relationship between pterygium and dry eye syndrome (DES), with conflicting results [5, 8, 9]. In addition, a very few studies have evaluated the effects of the excision of pterygium on tear function [10, 11]. …”
Section: Introductionmentioning
confidence: 99%
“…14 Wang S et al found that TBUT in the eyes with pterygium when compared with the opposite healthy eyes were significantly different (p < 0.05). 15 Rajab AY had found that mean TBUT in pterygium patients was 11.4±6 seconds while in control group the mean TBUT was 15±4.5 seconds. There was significant difference between the mean TBUT of the two groups.…”
Section: Tear Film Break Up Time (Tbut)mentioning
confidence: 96%